Let's End HepC: Modelling Public Health Epidemiological Policies Applied to Hepatitis C in Spain - Lopes, Henrique; Baptista-Leite, Ricardo; Franco, Diogo; Serra, Miguel A.; Escudero, Amparo; Martín-Moreno, José M. (Frontiers in Public Health, 2022)
Background: The WHO defined international targets towards the elimination of hepatitis C by 2030. Most countries are not on track to achieve this goal unless many challenges are surpassed. The Let’s End HepC (LEHC) tool aims to contribute to the control of hepatitis C. The innovation of this tool combines the modelling of public health policies (PHP) focused on hepatitis C with epidemiological modelling of the disease, obtaining a unique result that allows to forecast the impact of policy outcomes. The model was applied to several countries, including Spain. Methods: To address the stated objective, we applied the “Adaptive Conjoint Analysis” for PHP decision-making and Markov Chains in the LEHC modelling tool. The tool also aims to be used as an element of health literacy for patient advocacy through gamification mechanisms and country comparability. The LEHC project has been conducted in several countries, including Spain. The population segments comprised in the project are: PWID, Prisoners, Blood Products, Remnant population. Results: A total of 24 PHP related to hepatitis C were included in the LEHC project. It was identified that Spain had fully implemented 14 of those policies to control hepatitis C. According to LEHC’s model forecast, the WHO’s Hepatitis C elimination goal on reducing the number of patients living with Hepatitis C to 10% can be achieved in Spain by 2026 if current policies are maintained. The model estimates that the total population in Spain, by 2026, is expected to comprise 26,367 individuals living with hepatitis C. Moreover, if the 24 PHP considered for this study are fully implemented in Spain, the elimination goal may be achieved in 2024, with 29,615 individuals living with hepatitis C by that year. Conclusion: The findings corroborate the view that Spain has set great efforts in directing PHP towards HCV elimination by 2030. However, there is still room for improvement, namely in further implementing 10 of the 24 PHP considered for the LEHC project. By maintaining the 14 PHP in force, the LEHC model estimates the HCV elimination in the country by 2026, and 2024 if further measures are employed to control the disease.